Assessing Entrepreneurial Characteristics among Public University Students in Ethiopia (Global Journal of Management and Business Research, 2015)
Purpose: purpose of this study aims at assessing entrepreneurial characteristics among public university students in Ethiopia. Methodology: Survey research method was employed involving total of 210 students from four public Universities found in the Ethiopia. Sample of respondents from selected Universities were drawn by using systematic sampling techniques. The study used both primary and secondary data. Pertaining to data analysis both qualitative and quantitative data analysis techniques mainly descriptive analysis using percentages, tables and graphs were employed. While for inferential statistics like distribution based of determinant factors of entrepreneurial intention undergraduate students multiple regression analysis was conducted to identify which variables are significant for the model. Regression analysis was used to explain the effect of independent variables on a dependent variable.
Keywords: percentages; tables and graphs were employed